SYIAH DI TASIKMALAYA: PENGELOLAAN KERUKUNAN DENGAN KOMUNITAS LAIN - Ibnu Hasan Muchtar (Harmoni, 2017)
This paper looks at the development of Shi‘i movement that currently becomes a public discourse, especially after the foundation of an organisation which rejects the presence of Shi‘ism in Indonesia. Based on the study conducted by using qualitative method and case-study approach, this paper indicates the harmonious relationship between the Shi‘i and non-Shi‘i groups in Tasikmalaya. This has been marked by the absence of conflict between both groups. Some Shi‘i figures associated to IJABI (Ikatan Jamaah Ahlul Bayt Indonesia) and public and religious figures in Tasikmalaya, know each other personally. There have been good collaborations between community members in many socio-cultural events such as gotong-royong (mutual-cooperation), the celebration of religious festivals, national days in grass-root levels. Yet there have been rejection in the forms of rally and the declaration of ANAS (Aliansi Nasional Anti Syi’ah, National Alliance of Anti-Shi‘ism). This, however, mostly caused by the use of social media.